2015
DOI: 10.3233/jad-142769
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dementia in People Aged 60 Years and Above: Results from the WiSE Study

Abstract: The establishment of accurate data on the number of people with dementia is essential in the planning of services and initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
145
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 133 publications
(148 citation statements)
references
References 24 publications
3
145
0
Order By: Relevance
“…The collection of research data without participant’s identifiers such as name, and other identifiable data further ensured confidentiality . The study method has been described in detail elsewhere [32]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collection of research data without participant’s identifiers such as name, and other identifiable data further ensured confidentiality . The study method has been described in detail elsewhere [32]. …”
Section: Methodsmentioning
confidence: 99%
“…It has a multiethnic urban population comprising Chinese, Malays and Indians as well as those belonging to other ethnicities. A recent study in Singapore [32] examined the risk factors of dementia and identified that older age, lower education, homemaker and retired status, and a history of stroke diagnosis were associated with a higher risk of dementia. Although various studies have demonstrated possible modifiable health and lifestyle risk factors of dementia, few studies have examined the pathways of how these factors influence each other as mediators and moderators that subsequently lead to dementia.…”
Section: Introductionmentioning
confidence: 99%
“…These disorders were chosen for three main reasons. First, these disorders were previously explored in local epidemiological studies and were identified as common disorders in Singapore -major depressive disorder, alcohol abuse and OCD being the top three most common disorders and dementia having a prevalence of 10% in the older adult population (Chong et al 2012c;Subramaniam et al 2015). Second, these disorders were associated with large treatment gaps (Chong et al 2012a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The decline in cognitive functions, especially learning and memory deficits, is prevalent among older adults, which results in degraded quality of life for them [1,2]. Therefore, how to slow down the impairments of learning and memory in the aging process to promote the development of cognitive function is one of the goals of public health.…”
Section: Introductionmentioning
confidence: 99%